Redesain Pasar Tradisional Jibama Di Jayawijaya Wamena Papua: Bahasa Indonesia - Ronald Kogoya; I Wayan Parwata; I Nyoman Gede Maha Putra (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
ABSTRACT Jibama Traditional Market is one of the biggest trading center markets in Hubikiak District, Jayawiaya Regency, Wamena Papua. Nearly 85% of Jayawijaya people still depend on traditional markets, especially the lower middle class. As for those in the traditional jibama market, the problems include; [1] the condition of the damaged buildings looks ancient/old, the column and interior beam structures are weathered, there is no difference between booths and kiosks/shops, there is no space grouping according to the type of merchandise, selling table standards that are not in accordance with general standards, an increase in traders that exceed the market capacity that is already local government, circulation of vehicles, human goods that have not been properly managed, live pig stalls that are not in accordance with standards that make pig livestock traders have to tie pigs in in front of the market front for sale, the drainage system is not good [2] there is no grouping of parking lots according to their respective functions such as visitor parking, parking management, merchant parking, there is no proper arrangement of district and city public transportation terminals, roads in the market that have been damaged and destroyed [3] zoning in market areas that are not optimal. From some of the problems above, it is necessary to redesign the Jibama Traditional Market in Jayawijaya Wamena Papua so that it can answer the problems above for safety, comfort, activities for visitors, traders, and good management. Keywords: Jibama Traditional Market Redesign in Jayawijaya Wamena Papua